New multitarget directed benzimidazole‐2‐thiol‐based heterocycles as prospective anti‐radical and anti‐Alzheimer's agents. Issue 2 (8th September 2020) - Latif, Abdul; Bibi, Samina; Ali, Sardar; Ammara, Ammara; Ahmad, Manzoor; Khan, Ajmal; Al‐Harrasi, Ahmed; Ullah, Farhat; Ali, Mumtaz
Abstract: A series of new heterocycles (4 –18 ) was synthesized by the structural modification of benzimidazole‐2‐thiol (BT, 2‐MBI). The structures of the synthesized compounds were confirmed with the help of high‐resolution mass spectrometry (HRMS) and 1 HNMR spectroscopy. High inhibitions of the oxidants such as ABTS and DPPH were observed for compounds 9 [IC50 (s) = 167.4 μM (ABTS), 139.5 μM (DPPH)], 10 [IC50 (s) = 186.5 μM (ABTS), 155.4 μM (DPPH)], 11 [IC50 (s) = 286.1 μM (ABTS), 189.1 μM (DPPH)], 12 [IC50 (s) = 310.8 μM (ABTS), 162.2 μM (DPPH)], 14 [IC50 (s) = 281.3 μM (ABTS), 205.7 μM (DPPH)], 15 [IC50 (s) = 284.1 μM (ABTS), 177.3 μM (DPPH)], and 16 [IC50 (s) = 344.7 μM (ABTS), 270.2 μM (DPPH)] as compared with Ascorbic acid [IC50 (s) = 340.9 μM (ABTS), 164.3 μM (DPPH)]. The anti‐Alzheimer's activity was performed in vitro against cholinesterase enzymes (AChE, BChE). Compound 11 was able to show significant inhibitions [IC50 (s) = 121.2 μM (AChE), 38.3 μM (BChE)] as against that of galantamine [IC50 (s) = 139.4 μM (AChE), 40.3 μM (BChE)]. Compound 14 was found as a very good inhibitor of butyrylcholinesterase (IC50 = 35.4 μM) as compared with standard galantamine. Molecular docking was further performed to investigate the mechanism of anticholinesterase activity.